Molecular and electronic structure elucidation of Fe2+/Fe3+ complexed chelators used in iron sulphide scale removal in oil and gas wells. (15th March 2019) - Onawole, Abdulmujeeb T.; Hussein, Ibnelwaleed A.; Sultan, Abdullah; Abdel‐Azeim, Safwat; Mahmoud, Mohamed; Saad, Mohammed A.
ABSTRACT: Quantum chemical calculations based on DFT are employed to study the electronic structure and binding affinity of chelators used in the removal of iron sulphide scales. Three chelating agents, EDTA, HEDTA, and DTPA, are considered in this work. The complexes showed a coordination number of 5, 6, and 7 for Fe 2+ and Fe 3+ ions with HEDTA, EDTA, and DTPA, respectively. However, regarding EDTA, Fe 3+ could coordinate with an additional water molecule and form a seven‐coordinate complex. The calculated binding energies agreed with the experimental stability constants of the chelators in the order DTPA > EDTA > HEDTA for both Fe 2+ /Fe 3+ complexes. The binding free energies showed a spontaneous reaction with Fe 3+ having a stronger binding affinity than Fe 2+ due to electrostatic forces. This investigation provides insights regarding how chelators that are applied in iron sulphide scale removal may be designed by increasing the number of nitrogen atoms to above the number of carboxylate groups. Abstract : Structure of Fe 3+ ‐DTPA %: dark brown‐iron, blue‐nitrogen, red‐oxygen, white‐hydrogen, light brown‐carbon, and purple line‐coordination bonds.